Three-Year Survival Comparison Between Transcatheter and Surgical Aortic Valve Replacement for Intermediate- and Low-Risk Patients. Issue 3 (May 2018) - Siordia, Juan A.; Loera, Jackquelin M.; Scanlon, Matt; Evans, Jessie; Knight, Peter A.
Abstract : Abstract: Transcatheter aortic valve implantation is a suitable therapeutic intervention for patients deemed inoperable or high risk for surgical aortic valve replacement. Current investigations question whether it is a suitable alternative to surgery for intermediate- and low-risk patients. The following meta-analysis presents a comparison between transcatheter versus surgical aortic valve replacement in patients that are intermediate and low risk for surgery. Articles were collected via an electronic search using Google Scholar and PubMed. Articles of interest included studies comparing the survival of intermediate- and low-risk patients undergoing transcatheter aortic valve implantation to those undergoing surgical aortic valve replacement. Primary end points included 1-, 2-, and 3-year survival. Secondary end points included postintervention thromboembolic events, stroke, transient ischemic attacks, major vascular complications, permanent pacemaker implantation, life-threatening bleeding, acute kidney injury, atrial fibrillation, and moderate-to-severe aortic regurgitation. Six studies met the criteria for the meta-analysis. One- and two-year survival comparisons showed no difference between the two interventions. Surgical aortic valve replacement, however, presented with favorable 3-year survival compared with the transcatheter approach. Transcatheter aortic valve implantation had more major vascular complications, permanent pacemaker implantation, and moderate-to-severe aortic regurgitation rates compared with surgery. Surgical aortic valve replacement presented more life-threatening bleeding, acute kidney injury, and atrial fibrillation compared with a transcatheter approach. There was no statistical difference between the two approaches in terms of thromboembolic events, strokes, or transient ischemic attack rates. Surgical aortic valve replacement presents favorable 3-year survival rates compared with transcatheter aortic valve implantation.